Preparation and characterization of alginate based-fluorescent magnetic nanoparticles for fluorescence/magnetic resonance multimodal imaging applications. (1st May 2018) - Kwon, Yong-Su; Choi, Kee-Bong; Lim, Hyungjun; Lee, Sunghwi; Lee, Jae-Jong
Abstract: Simple and versatile methodologies have been reported that customize the surface of superparamagnetic iron oxide (SPIO) nanoparticles and impart additional fluorescence capabilities to these contrast agents. Herein, we present the rational design, synthesis, characterization, and biological applications of a new magnetic-based fluorescent probe. The dual modality imaging protocol was developed by labeling fluorophore with alginate natural polymers that have excellent biocompatibility and biodegradability, and using gelification method to form nanocomposites containing SPIO. The formation of alginate-based fluorescent magnetic (AFM) nanoparticles was observed in spherical and elliptical forms with a diameter of less than 500 nm by a transmission electron microscope (TEM). The fluorescent wavelength band in the range of 560 nm was also confirmed in the UV–visible spectrophotometer. In this study, we demonstrate that the multi-tasking design of AFM nanoparticles provides an ideal platform for building balanced dual-image probes of magnetic resonance imaging and optical imaging.